Effect of operating conditions on acoustic gas metering in the Niger Delta (2011)
This study investigated the relationship between velocity of sound and properties of natural gases under different equations of state and the operational implications on acoustic gas metering. The velocity of sound was related to the thermodynamic properties of natural gas using both the Soave-Redlich-Kwong (SRK) and Peng-Robinson (PR) equations of state and applied to 5 wet and 5 dry natural gas samples from the Niger Delta at different conditions of temperature and pressure. Predicted results were statistically analyzed and compared with experimental data. For wet gas, SRK and PR equations gave average absolute deviation (AAD) of 9.50% and 1.15% for velocity of sound respectively: while AAD of 0.943% and 7.021% were obtained for dry gas using the SRK and PR equations respectively. Predictions of sonic velocity and gas properties using both SRK and PR tend to give higher accuracy at high pressures than at ambient pressures and temperatures suggesting that correction factors must be implemented tor ambient metering of gases when acouistic meters are used.